Women depiction in Gulliver’s travels by Jonathan Swift - Avila Neto de Farias, Ariane (Entrelaces - Revista do Programa de Pós-Graduação em Letras-UFC, 2020)
This paper aims at analyzing the work Gulliver’s Travels (2009) by Jonathan Swift from a gender perspective. As object of this research it was taken the Queen’s maid of honor of Brondingnag. The present analyses showed that in a first glance it is possible to think in a reality in which the woman is not described as subdued to the masculine. However, it is highlighted that women still assimilate a submissive role and do not subvert the establishment imposed by their gender. Hence, no change occurs in woman representation because the female characters are impregnated by male discourse. Thus, because of strong cultural issues the Queen’s maid act according to the expectations the Western patriarchal society has about them.